Volume and turn-of-the-year behavior - Lakonishok, Josef; Smidt, Seymour (Journal of Financial Economics, 1984)
This paper studies the trading characteristics of listed companies by size, and year-end behavior. There were no transactions on nearly 25% of the days for the smallest decile even at the turn of year which is an active trading period for small companies. As a result of low levels of trading and the regulations governing exchange specialists, transaction prices and quotations of small listed companies may require several days to fully reflect equilibrium price changes. The data confirm the existence of a year-end seasonal pattern in rates of return for small companies and suggest that there may be a seasonal pattern for large companies as well.